Regulation of Information Relations in CustomsAuthorities of the Russian Federation (on the Example of Measures for EnsuringInformation Security and Protection of Intellectual Property) - Sergey Nikolaevich Klimenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article discusses some of the aspects that define the role and place of legal regulation of information relations arising in the sphere of ensuring information security of the customs bodies of the Russian Federation.